Effects of the Production Process on Quality of Gymnema inodorum (Lour.) Decne. Powder and Enhancing Their Quality of Herbal Tea Mixtures of the Phu Phan Development Study Center Community Enterprise, Pla Pak District, Nakhon Phanom Province - Chunwijitra, Krittika; Phunthupan, Phakorn; Phesatcha, Burarat; Thiwato, Sutthida; Phesatcha, Kampanat (YRU Journal of Science and Technology, 2024)
The Chiang Da tea products mixed with herbs, are product developed by the Phu Phan Development Study Center Community Enterprise. A problem was found in the production and product quality. This study aimed to examine the effects of the production process on the quality of Gymnema inodorum (Lour.) Decne. powder and to improve the quality of tea products mixed with herbs. Three production methods were compared, namely drying in a hot air oven at 50 ◦C for 240 minutes (method 1), blanching at 90 ◦C for 30 seconds and drying in a hot air oven at 50 ◦C for 240 minutes (method 2), and blanching at 90 ◦C for 30 seconds, roasting for 10 minutes, and drying in a hot air oven at 50 ◦C for 240 minutes (method 3). The findings discovered that blanching before drying in a hot air oven made Chiang Da powder bright green with maximum lightness (L*), greenness (-a*) and yellowness (b*) values. The total phenolic compound was 68.27 mg GAE/g DW and the antioxidant activity using DPPH radical scavenging activity was at 24.06 %. When the developed Chiang Da powder was used to produce Chiang Da tea mixed with herbs, the product had moisture value, total microbial counts, yeast and mold according to community product standards. The total phenolic compound was 44.13 mg GAE/g DW and the antioxidant activity was 24.02 %. Therefore, the Chiang Da powder with the production process of blanching at 90 ◦C for 30 seconds and drying at 50 ◦C for 240 minutes was appropriate.